Makna Dan Nilai Pedagogis-Teologis Dalam Tradisi Waura Watu Pada Masyarakat Anakalang, Sumba Tengah - Daud Saleh Luji; Yohanis Sebu Kuala; Simon Kasse; Lanny Koroh (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
The title raised in this study is Pedagogical-Theological Meaning in the Waura Watu Tradition in the Anakalang Community, Central Sumba. The purpose of this study was to describe and analyze the dynamics of the perceptions of the Anakalang people and the pedagogical-theological meaning of the waura watu (stone pulling) grave tradition in the Anakalang community, Central Sumba. This type of research is qualitative research with in-depth interview techniques conducted on key informants, namely traditional leaders, traditional practitioners, religious leaders, and the organizers of the stone pulling ritual. The results of the study show that the tradition of pulling gravestones has an important meaning in the traditions of the Sumba people, especially to honor or respect their ancestors. Since hundreds of years ago until now. The grave stones in Anakalang have a function that cannot be replaced until now, even though graves are known to be made of cement. The erection of grave stones and the tradition of stone pulling are integrated into the daily life of the Anakalang people against a background of religious conceptions which are seen as the legacy of their ancestors which must be upheld, because they have pedagogical values, namely mutual cooperation, unity in society, kinship, culture and deep theological values. That is why the variety of stone-pulling culture in Sumba has penetrated the theoretical time period and has continued until now as a tradition.